Protective effect of melatonin against age-related ischemia-reperfusion injury is associated with the NLRP3 inflammasome pathway - Ikram Ben Jeddou; Ángela Berlana; Esther Rey; Hassen Ben Abdennebi; Wassim Y. Almawi; Abdelwahab Omri; Ángela M. Valverde; Águeda González-Rodriguez; Mohamed Amine Zaouali (Journal of Physiology and Biochemistry, 2026)

First Report of Gynandromorphism in Rhipicephalus microplus (Acari: Ixodidae) in El Salvador - Marvin Stanley Rodriguez Aquino; Esther Noemí Juárez Alvarado; Francisco Javier Castaneda Lúe; Pamela Michelle Cornejo Rivas; Melissa S. Nolan; Lídia Gual-Gonzalez (Acta Parasitologica, 2026)
Purpose Gynandromorphism is a developmental anomaly characterized by the simultaneous presence of male and female sexual morphological traits within the same individual. This study documents a case of gynandromorphism in the cattle tick Rhipicephalus microplus (Canestrini 1888) in El Salvador. Methods The specimen was collected from a bovine belonging to the Experimental and Practical Station of the Faculty of Agronomic Sciences of the University of El Salvador, located in the municipality of San Luis Talpa, Department of La Paz. Results The reported gynandromorph of R. microplus exhibits bilateral gynandromorphism, displaying primarily female characteristics on the left side and male characteristics on the right. Conclusion This is the first report of a tick with gynandromorphism in El Salvador. Further studies are warranted to understand the implications of such anomalies and their veterinary and public health relevance.

Occurrence of Organic Micropollutants in the Water Cycle of a Euro-Mediterranean Resort: A Case Study - Lucia Gusmaroli; Josephine Vosse; Esther Mendoza; Ignasi Rodriguez-Roda; Giuliana Ferrero; Gianluigi Buttiglieri (Water, Air, & Soil Pollution, 2026)
Tourism can affect the availability and quality of freshwater resources, particularly in coastal regions like the Mediterranean. Water reuse is an increasingly adopted practice aimed at enhancing water resilience. To reduce pressure on freshwater resources, it is also being implemented in tourism-intensive areas at both centralised and decentralised scales. As a result, its potential environmental and public health risks are increasingly being investigated. At present, very few studies reported on the occurrence of organic micropollutants (OMP) in closed water cycles related to tourism, and to the best of the authors’ knowledge, only one of them differentiated their occurrence in the different water and wastewater streams. This article investigates the occurrence of a set of OMP in the water cycle of a large resort located in Lloret de Mar, Spain. It hereby considers tap and pool water, the separate greywater streams (kitchen, laundry, and bathroom greywater, where part of the greywater is reused for toilet flushing), and wastewater. The target compounds include 39 OMP: 10 endocrine disruptors and related compounds (EDCs) and 29 pharmaceuticals (PhACs), most of them scarcely studied in the context of tourism in most investigated matrices, especially greywater, and some here reported for the first time. Two sampling campaigns were performed in the high and low tourist seasons. OMP were ubiquitous, with the lowest total concentrations found in tap water, as expected (124 ng/L), and the highest, amounting to 315 μg/L, in wastewater in the low season. Kitchen greywater, one of the least previously studied matrices, resulted in the highest total EDCs concentration. The highest total concentration of PhACs, 185 μg/L, was found in wastewater in the low season. Daily per capita OMP loads in wastewater and greywater are also provided, proving the variability of loads in the wastewater streams of the same facility between seasons, contributing to a more differentiated understanding about their quality and impact on the total wastewater load.

Effect of Peruvian sisal fiber on the mechanical and microstructural strength of concrete - Sócrates Pedro Muñoz Pérez; Miguel Alarcón Peltroche; Esther Teodora Eugenio Pachas; Luigi Italo Villena Zapata; Ana Paula Bernal Izquierdo; Ernesto Dante Rodriguez Lafitte; Miguel Ernesto Rodriguez Núñez; Juan Martín García Chumacero (Innovative Infrastructure Solutions, 2025)

The importance of tropical tree-ring chronologies for global change research - Peter Groenendijk; Flurin Babst; Valerie Trouet; Ze-Xin Fan; Daniela Granato-Souza; Giuliano Maselli Locosselli; Mulugeta Mokria; Shankar Panthi; Nathsuda Pumijumnong; Abrham Abiyu; Rodolfo Acuña-Soto; Eduardo Adenesky-Filho; et al. (Quaternary Science Reviews, 2025)

An Injectable Solution for Preservation of Hematopoietic Stem and Progenitors Cells in Hypothermic Condition - Jean Chevaleyre; Laura Rodriguez; Esther Attebi; Pascale Duchez; Zoran Ivanovic (Stem Cell Reviews and Reports, 2025)

Cooling rate modifies the location of aquaporin 3 in spermatozoa of sheep and goat - Belén Pequeño; María Gemma Millán de la Blanca; Cristina Castaño; Adolfo Toledano-Díaz; Milagros Cristina Esteso; Esther Alba; Francisco A. Arrebola; Rodolfo Ungerfeld; Belén Martínez-Madrid; Manuel Alvarez-Rodriguez; Heriberto Rodriguez-Martinez; Julián Santiago-Moreno (Theriogenology, 2024)

Correction: Tick-Borne Pathogens Screening Using a Multiplex Real-Time Polymerase Chain Reaction-Based Method - Sergio Andres Cardenas-Cadena; Maria Eugenia Castañeda-Lopez; Fabiana Esther Mollinedo-Montaño; Sodel Vazquez-Reyes; Jorge Lara-Arias; Ivan Alberto Marino-Martinez; Iram Pablo Rodriguez-Sanchez; Idalia Garza-Veloz; Margarita L. Martinez-Fierro (Acta Parasitologica, 2024)

MaPPeRTrac: A Massively Parallel, Portable, and Reproducible Tractography Pipeline - Lanya T. Cai; Joseph Moon; Paul B. Camacho; Aaron T. Anderson; Won Jong Chwa; Bradley P. Sutton; Amy J. Markowitz; Eva M. Palacios; Alexis Rodriguez; Geoffrey T. Manley; Shivsundaram Shankar; Peer-Timo Bremer; et al. (Neuroinformatics, 2024)

Kynurenine attenuates mitochondrial depolarization and neuronal cell death induced by rotenone exposure independently of AhR-mediated parkin induction in SH-SY5Y differentiated cells - Rosario García-Aguilar; Arturo Ortega; Esther López-Bayghen; Leticia Ramírez-Martínez; Ada Rodriguez-Campuzano; Fátima Murillo-González; Guillermo Elizondo; Libia Vega (NeuroToxicology, 2023)

Tick-Borne Pathogens Screening Using a Multiplex Real-Time Polymerase Chain Reaction-Based Method - Sergio Andres Cardenas-Cadena; Maria Eugenia Castañeda-Lopez; Fabiana Esther Mollinedo-Montaño; Sodel Vazquez-Reyes; Jorge Lara-Arias; Ivan Alberto Marino-Martinez; Iram Pablo Rodriguez-Sanchez; Idalia Garza-Veloz; Margarita L. Martinez-Fierro (Acta Parasitologica, 2023)
Purpose This study aims to develop and evaluate a cost-effective, user-friendly multiplex quantitative real-time polymerase chain reaction (qPCR) method for detecting multiple tick-borne pathogens associated with human and veterinary diseases. Methods In silico PCR was performed to design and evaluate primer sequences reported for amplifying Rickettsia spp ., Borrelia spp. , and Ehrlichia spp. Single and multiplex qPCR assays were then standardized to detect individual pathogens and multiple pathogens in a single reaction. Positive controls were generated to determine the dynamic range of the methods. In the validation phase, a total of 800 samples were screened for the presence of tick-borne pathogens. Results Identification in a single qPCR reaction (multiplex) of Ehrlichia spp . , and Borrelia spp. with a limit of detection of 10 copies and Rickettsia spp . with 100 copies, a PCR efficiency (E) of 90–100% and a coefficient of correlation ( R 2 ) of 0.998–0.996 for all pathogens. Conclusion The ability to detect three significant pathogens (Ehrlichia spp ., Rickettsia spp ., and Borrelia spp .) in a single qPCR reaction offers a significant advantage in the field of molecular diagnostics for tick-borne diseases. This advancement has a profound impact on public health as it facilitates the selection of appropriate treatment protocols, thereby reducing complications associated with disease progression. The streamlined approach provided by this method simplifies the diagnostic process and enables timely intervention, ultimately improving patient outcomes and mitigating the potential risks associated with untreated or misdiagnosed tick-borne infections.

Plant-based diets and risk of frailty in community-dwelling older adults: the Seniors-ENRICA-1 cohort - Javier Maroto-Rodriguez; Mario Delgado-Velandia; Rosario Ortolá; Adrián Carballo-Casla; Esther García-Esquinas; Fernando Rodríguez-Artalejo; Mercedes Sotos-Prieto (GeroScience, 2023)
Frailty is a geriatric syndrome that leads to increased risk of hospitalization, disability, and death. The effect of plant-based diets defined by the quality of their plant foods is unclear. Our objective is to study the association between two plant-based diet indices and the occurrence of frailty among community-dwelling older adults in Spain. We analyzed data from 1880 individuals aged ≥ 60 years from the Spanish Seniors ENRICA-1 cohort. We used a validated diet history to build two indices: (a) the healthful Plant-based Diet Index (hPDI) where healthy plant foods received positive scores, whereas less-healthy plant foods and animal foods received reverse scores; and (b) the unhealthful Plant-based Diet Index (uPDI), with positive scores to less-healthy plant foods and reverse scores to animal and healthy plant foods. Incident frailty was defined with the Fried phenotype. Study associations were summarized with odds ratios (OR) and 95% confidence intervals (CI) obtained from multivariable logistic models. After 3.3 years of follow-up, 136 incident frailty cases were ascertained. Comparing the highest vs. the lowest tertile of adherence, the OR [95% CI] for frailty was 0.43 (0.25–0.74; p- trend = .003) for the hPDI, and 2.89 (1.73–4.84; p- trend < .001) for the uPDI. Higher consumption of healthy plant foods was inversely associated with frailty (0.39 [0.23–0.66; p -trend < 0.001]); higher consumption of unhealthy plant foods was associated with higher frailty risk (2.40 [1.23–4.71; p -trend = .01]). In older adults, the hPDI was associated with lower risk of frailty, while the opposite was found for the uPDI.

Artifacts classification and apnea events detection in neck photoplethysmography signals - Irene García-López; Renard Xaviero Adhi Pramono; Esther Rodriguez-Villegas (Medical & Biological Engineering & Computing, 2022)
The novel pulse oximetry measurement site of the neck is a promising location for multi-modal physiological monitoring. Specifically, in the context of respiratory monitoring, in which it is important to have direct information about airflow. The neck makes this possible, in contrast to common photoplethysmography (PPG) sensing sites. However, this PPG signal is susceptible to artifacts that critically impair the signal quality. To fully exploit neck PPG for reliable physiological parameters extraction and apneas monitoring, this paper aims to develop two classification algorithms for artifacts and apnea detection. Features from the time, correlogram, and frequency domains were extracted. Two SVM classifiers with RBF kernels were trained for different window (W) lengths and thresholds (Thd) of corruption. For artifacts classification, the maximum performance was attained for the parameters combination of [W = 6s-Thd= 20%], with an average accuracy= 85.84%(ACC), sensitivity= 85.43%(SE) and specificity= 86.26%(SP). For apnea detection, the model [W = 10s-Thd= 50%] maximized all the performance metrics significantly (ACC= 88.25%, SE= 89.03%, SP= 87.42%). The findings of this proof of concept are significant for denoising novel neck PPG signals, and demonstrate, for the first time, that it is possible to promptly detect apnea events from neck PPG signals in an instantaneous manner. This could make a big impact in crucial real-time applications, like devices to prevent sudden-unexpected-death-in-epilepsy (SUDEP).

Linking inventories and impact assessment models for addressing biodiversity impacts: mapping rules and challenges - Esther Sanyé-Mengual; Antonio Valente; Fabrizio Biganzoli; Martin Dorber; Francesca Verones; Alexandra Marques; Jorge Ortigosa Rodriguez; Valeria De Laurentiis; Simone Fazio; Serenella Sala (The International Journal of Life Cycle Assessment, 2022)
Purpose An adequate matching between the nomenclature of elementary flows in life cycle inventory (LCI) databases and life cycle impact assessment (LCIA) methods is key for ensuring the proper application of life cycle assessment (LCA). However, the nomenclature of elementary flows lacks harmonization among the LCA community. This paper aims at defining mapping rules and discussing main challenges related to the process of systematically mapping LCI nomenclatures to LCIA methods and models addressing biodiversity impacts. Methods Eight LCIA methods and models addressing biodiversity loss are analyzed: five comprehensive LCIA methods (i.e., LC-IMPACT, Impact World + , Ecological Scarcity 2013, ReCiPe 2016, and Stepwise), one land use intensity-specific LCIA model; and two approaches adapting the GLOBIO model to LCIA. These models and methods are mapped to two LCI nomenclatures (ecoinvent v3.6 as implemented in Simapro and Environmental Footprint (EF) 3.0). A mapping tool was developed to support the process of (a) mapping elementary flows by name, Chemical Abstract Service number or available synonyms; (b) implementing specific mapping rules regarding compartment/sub-compartment, and substance name; (c) mapping elementary flows to manually defined proxies (e.g., synonyms, spelling corrections and similar substances); and (d) assigning characterization factors (CFs). The process entails analyzing a case study to identify uncharacterized elementary flows. Results and discussion We present a mapping of LCIA methods and models addressing impacts on biodiversity loss with specific LCI nomenclatures. Mapping rules are proposed for elementary flows regarding chemicals, carbon emissions, land use, water use, and particulate matter. Specific aspects to be considered in mapping elementary flows in LCIA and LCI nomenclatures are discussed. Main gaps in LCI nomenclatures are associated to toxicity and climate change impacts. The EF 3.0 was more aligned than ecoinvent 3.6 with the LCIA methods and models regarding elementary flows coverage and regionalization level. Analyzing uncharacterized flows revealed further coverage needs for “Chemical, organic” (between 19 and 20% uncharacterized flows), “Chemical, inorganic” (between 9 and 18% uncharacterized flows) and “Chemical, radioactive” (between 9 and 14% uncharacterized flows). Conclusions This paper contributes to the operationalization of LCIA methods and models addressing biodiversity impacts by proposing a systematic mapping process and rules for a better LCIA-LCI connection. Different development pathways of LCI (e.g., focused on substance name detail) and LCIA (e.g., towards improved regionalization level) have stretched the gap between both nomenclatures. Recommendations are provided identifying further efforts towards the harmonization of the nomenclature of elementary flows in the LCA community.

Doubting dung: eDNA reveals high rates of misidentification in diverse European ungulate communities - Robert Spitzer; Marcin Churski; Annika Felton; Marco Heurich; Dries P. J. Kuijper; Marietjie Landman; Esther Rodriguez; Navinder J. Singh; Pierre Taberlet; Suzanne T. S. van Beeck Calkoen; Fredrik Widemo; Joris P. G. M. Cromsigt (European Journal of Wildlife Research, 2019)

Removal of imidazolium- and pyridinium-based ionic liquids by Fenton oxidation - Esther Gomez-Herrero; Montserrat Tobajas; Alicia Polo; Juan J. Rodriguez; Angel F. Mohedano (Environmental Science and Pollution Research, 2018)

Comparing the impact of a grazing regime with European bison versus one with free-ranging cattle on coastal dune vegetation in the Netherlands - E. Valdés-Correcher; Esther Rodriguez; Yvonne J. M. Kemp; Martin J. Wassen; Joris P. G. M. Cromsigt (Mammal Research, 2018)

How can leadership processes in European bison be used to improve the management of free-roaming herds - Amandine Ramos; Lola Manizan; Esther Rodriguez; Yvonne J. M. Kemp; Cédric Sueur (European Journal of Wildlife Research, 2018)

Carriage of One or Two FMR1 Premutation Alleles Seems to Have No Effect on Illness Severity in a FXTAS Female with an Autozygous FMR1 Premutation Allele - Laia Rodriguez-Revenga; Javier Pagonabarraga; Beatriz Gómez-Anson; Olga López-Mourelo; Silvia Izquierdo; Maria Isabel Alvarez-Mora; Esther Granell; Irene Madrigal; Montserrat Milà (The Cerebellum, 2016)

Erratum to: Optimal features for online seizure detection - Lojini Logesparan; Alexander J. Casson; Esther Rodriguez-Villegas (Medical & Biological Engineering & Computing, 2016)

The impact of signal normalization on seizure detection using line length features - Lojini Logesparan; Esther Rodriguez-Villegas; Alexander J. Casson (Medical & Biological Engineering & Computing, 2015)

A Low Computational Cost Algorithm for REM Sleep Detection Using Single Channel EEG - Syed Anas Imtiaz; Esther Rodriguez-Villegas (Annals of Biomedical Engineering, 2014)

Na/K pump regulation of cardiac repolarization: insights from a systems biology approach - Alfonso Bueno-Orovio; Carlos Sánchez; Esther Pueyo; Blanca Rodriguez (Pflügers Archiv - European Journal of Physiology, 2014)

A genome-wide association study of breast cancer in women of African ancestry - Fang Chen; Gary K. Chen; Daniel O. Stram; Robert C. Millikan; Christine B. Ambrosone; Esther M. John; Leslie Bernstein; Wei Zheng; Julie R. Palmer; Jennifer J. Hu; Tim R. Rebbeck; Regina G. Ziegler; et al. (Human Genetics, 2013)

Compressive sensing scalp EEG signals: implementations and practical performance - Amir M. Abdulghani; Alexander J. Casson; Esther Rodriguez-Villegas (Medical & Biological Engineering & Computing, 2012)

Optimal features for online seizure detection - Lojini Logesparan; Alexander J. Casson; Esther Rodriguez-Villegas (Medical & Biological Engineering & Computing, 2012)

Effect of salinity on egg hatching, yolk sac absorption and larval rearing of Senegalese sole ( Solea senegalensis Kaup 1858) - Emilio A. Salas Leitón; Ana Rodriguez‐Rúa; Esther Asensio; Carlos Infante; Manuel Manchado; Catalina Fernández‐Díaz; José P. Cañavate (Reviews in Aquaculture, 2012)
Assays carried out under laboratory‐controlled conditions revealed that eggs of Senegalese sole, Solea senegalensis Kaup 1858, incubated at 10, 18, 27 and 33 grams per litre (g L −1 ) reached their maximum hatching rates (above 80%) 48 h after incubation. In contrast, hatching was significantly delayed (24 h) and completely failed when the salinity was set at 5 and 0 g L −1 , respectively. Newly hatched and early‐developing yolk sac larvae presented similar survival rates 3 days after hatching (DAH) when exposed to salinities of 10, 18, 27 and 33 g L −1 . Larvae incubated at 5 g L −1 salinity died a few hours after hatching once they were released from their respective chorions. The notochord length was unmodified by salinity 5 DAH. Nevertheless, an overall lower myotomal height and a putative delay in the depletion of yolk sac were found in larvae reared at 10 g L −1 . This anomaly in overall larval development became more pronounced with the occurrence (100% of analysed larvae) of mouth deformities and a lack of functionality under 10 g L −1 salinity. Transferring 2 DAH larvae from 33 g L −1 (exhibiting normal mouth development) to a medium with a salinity of 10 g L −1 had no effect on first feeding, weight and metamorphic index. Overall our results indicate the existence of a key time window (0–2 DAH) in which a salinity value higher than 10 g L −1 is required to achieve adequate mouth development and further functionality of larvae. The present work represents a valuable contribution to the sole industry, opening new possibilities in hatchery management practices.

Myzus persicae is Arrested More by Blends Than by Individual Compounds Elevated in Headspace of PLRV-Infected Potato - Esther Ngumbi; Sanford D. Eigenbrode; Nilsa A. Bosque-Pérez; Hongjian Ding; Analiz Rodriguez (Journal of Chemical Ecology, 2007)

Cellular cardiomyoplasty: development of a technique to culture human myoblasts for clinical transplantation - M. Esther Rendal Vázquez; M. Rodriguez Cabarcos; T. Diaz Román; A. Juffé Stein; N. Doménech Garcia; B. Adrio Nazar; M.J. Sánchez Dopico; C. Andión Núñez; F.J. Blanco Garcia (Cell and Tissue Banking, 2005)

Enhancing effect of calcium and vanadium ions on thermal stability of bromoperoxidase from Corallina pilulifera - Esther Garcia-Rodriguez; Takashi Ohshiro; Toshiaki Aibara; Yoshikazu Izumi; Jennifer Littlechild (JBIC Journal of Biological Inorganic Chemistry, 2005)